INFLUENCE OF ASPHALT CONCRETE ROAD COEFFICIENT ON THE ROAD SURFACE - Tovboev , Baxrom (SAMBHRAM XABARNOMASI, 2024)
Annotation This article presents information about the traction coefficient of pavement with automobile tires.